Survey of Optimizing Link Sleeping Reconfigurations in ISP Networks (International Journal of Engineering and Computer Science, 2014)
The power consumption of the internet accounts has been increased in the bandwidth hungry applications. Several initiatives are being put into place to reduce the power consumption of the Information and Communication Technologies (ICT) sector. Network resource optimization has become one of the most important research areas in the field of ISP networks. Sleeping reconfiguration and rate adaptation has been used for reducing energy consumption when the traffic demands are at their low levels. In this work, an efficient heuristic based Time-driven Link Sleeping (TLS) is proposed for reducing the energy consumption. A robust TLS scheme with Single Link Failure Protection (TLS-SLFP) aims to achieve an optimized trade-off between network robustness and energy efficiency performance.